Analisis Pengaruh Literasi Keuangan Syariah dan Religiusitas terhadap Minat Berinvestasi di Pasar Modal Syariah (Studi Kasus Generasi Z di Kabupaten Pekalongan) - Falikhah, Anis Nala; Adinugraha, Hendri Hermawan; Sulthoni, Muhammad (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
Although the growth of the Islamic capital market is quite rapid, the level of participation of Generation Z in investing in the Islamic capital market is still relatively low. Factors that are often mentioned as the cause of low interest in investing in the Islamic Capital Market are the level of Sharia Financial Literacy and Religiosity. This study aims to analyse the effect of Sharia Financial Literacy and Religiosity on Gen Z's Investment Interest in the Islamic Capital Market. This research uses quantitative methods, data collected through online surveys using questionnaires distributed to 100 respondents of Gen Z Pekalongan Regency who have an interest in investing in the Islamic Capital Market, data analysis techniques using Multiple Regression Analysis with the help of SPSS 26.0 software. The results of the analysis show that Sharia Financial Literacy and Religiosity have a positive and significant effect on Interest in Investing in the Sharia Capital Market both partially and simultaneously.